Análise ergonômica de um posto de trabalho de soldagem elétrica em uma indústria metalmecânica - Moreira, David Fontenele (2016)
This work is a bibliographical research, qualitative, with the general objective of making an ergonomic analysis of the work safety conditions of an electric welding station. The research sought their sources in books and electronic addresses that brought issues of the theme. In his theoretical work is conducted to study and analyze the accident at work in general, however, in a welding station, the place that has been applied an ergonomic questionnaire, which is evidenced routine and care that a company It is in that respect the employee's physical integrity, offering them the least favorable working conditions. The research brings concepts of safety equipment, the correct way to use them, keep them, cleans them and discard them, teaching company and employee to prevent accident or occupational incidents. The work shows the most common types of occupational diseases in a job, while giving prevention tips through physical activities like gymnastics, which is most used by companies that have the concern to maintain a work environment free from occupational diseases. The survey is completed by ergonomic questionnaire to determine the care that a welding company has as to what concerns the security and combat accident in routine work.